Development Nutritional Evaluation and Acceptability of Moringa Moringa oleifera and Eel Monopterus albus Meatballs as a Functional Food for Stunted Toddlers - rahmat zarkasyi, rahmat zarkasyi; nurlinda , nurlinda; usman, usman; Muhammad Ikram, Muhammad Ikram (Tadulako University, 2025)
ABSTRACT Stunting remains a major nutritional problem in Indonesia with a relatively high prevalence, particularly in South Sulawesi. One cause is low nutritional intake in toddlers. Moringa leaves (Moringa oleifera) and eel (Monopterus albus) are local foods rich in protein, iron, and vitamins, but their utilization remains low. This study aims to determine the nutritional content and acceptability of a combination of moringa leaf and eel meatballs as a functional food for stunted toddlers. The study used an experimental design with two formulations: F1 (300 g eel: 30 g moringa leaves) and F2 (150 g eel: 15 g moringa leaves). Nutritional analysis was conducted in the laboratory, while acceptability testing was conducted on 6 mothers and 6 toddlers using a hedonic test. Laboratory test results showed that F1 had a higher protein content (5.68%) than F2 (4.02%), while F2 had higher carbohydrate (26.35%) and energy (125.17 kcal) than F1 (97.48 kcal). Organoleptic tests showed that respondents liked the color and texture of the meatballs (liked), while the aroma and flavor were quite liked. Thus, the combination of moringa leaf and eel meatballs has the potential to be a locally based functional food alternative to support toddler nutrition and can be used as an innovative strategy to reduce stunting rates in Indonesia. Keywords: stunting, toddlers, moringa leaf meatballs, eel, functional food